Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1055/s-0037-1609021
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Management of Pediatric Ulcerative Colitis

Abstract: Inflammatory bowel disease (IBD) describes a spectrum of idiopathic, lifelong, and progressive intestinal inflammatory conditions that includes Crohn's disease, ulcerative colitis, and indeterminate colitis. A worldwide increase in the incidence of IBD has been observed. In comparison to adults, IBD occurring during childhood and adolescence has several unique clinical characteristics and surgical management issues. In this article, we provide an overview contrasting these important differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 77 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Moreover, in pediatric patients, the pancolitis at onset is quite common with a natural course often more severe than for their adult counterparts. 16 Kelley-Quon et al 17 reported as predictive factors for colectomy a serum albumin less than 3.5 g/dL, significant weight loss at the time of diagnosis, and a first-degree relative with UC. Our patient had two of these predictive factors for colectomy in the future, and this, considering the underlying complex genitourinary–rectal malformation, is of a great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in pediatric patients, the pancolitis at onset is quite common with a natural course often more severe than for their adult counterparts. 16 Kelley-Quon et al 17 reported as predictive factors for colectomy a serum albumin less than 3.5 g/dL, significant weight loss at the time of diagnosis, and a first-degree relative with UC. Our patient had two of these predictive factors for colectomy in the future, and this, considering the underlying complex genitourinary–rectal malformation, is of a great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for toxic megacolon include CMV or C. difficile infection, hypokalemia, hypomagnesemia, and the use of drugs that decrease colonic motility, such as anticholinergics, narcotics, and antidepressants with anticholinergic properties (207) . Additionally, early discontinuation or rapid reduction of steroids or aminosalicylates and diagnostic procedures that can cause colonic distention (colonoscopy and barium enema) are also risk factors for the development of toxic megacolon (208) . Children with toxic megacolon should be treated by surgeons and conservative management should only be considered in stable clinical conditions and in highly specialized centers under close monitoring; urgent colectomy is recommended if no improvement is apparent within 24 to 72 hours (22) .…”
Section: Recommendationmentioning
confidence: 99%
“…Pediatric IBD patients should be screened frequently for these disorders, as well as for impairments in social functioning, and referred appropriately [13]. A surgeon should be consulted for those who fail medical management or have disease-related complications that require it, such as dysplasia, perforations, and obstructions [14,15].…”
Section: Multidisciplinary Approachmentioning
confidence: 99%